Membangun Subjektifitas dalam Fotografi Melalui Metode Integratif - Rahadi, Panji Firman; Ridwan, Iwan Muhammad; Perdana, Bayu Bambang (Wacadesain, 2025)
Subjectivity in photography is not innate phenomenon but rather the result of a creative process that is inherently reflective and contextually situated. This study proposes the development of an integrative methodological framework that synthesizes the principles of visual exploration (EDFAT) with the visual rhetoric model articulated by Wendy Hesford and Brenda Brueggmann. Employing a constructivist Grounded Theory approach, the research systematically examines gow photographers cultivate an awareness of identity, positionality and audience engagement through visual practices. The methodological framework is intended to contribute to a deeper theoretical and practical understanding of subjectivity within the practice of photography.